Parenting style and children emotion management skills among Chinese children aged 3–6: the chain mediation effect of self-control and peer interactions - Li, Dexian; Li, Wencan; Zhu, Xingchen (Frontiers in Psychology, 2023)
Drawing on ecosystem theory, which is based on the interaction of family environment, individual characteristics, and social adaptation, this study aimed to examine the effects of parenting style on emotion management skills and the mediating roles of self-control and peer interactions among Chinese children aged 3-6 years. Some studies have investigated the relationship between parenting style and emotion management skills. However, research on the underlying mechanisms is still deficient. A sample of 2303 Chinese children completed the PSDQ-Short Version, the Self-Control Teacher Rating Questionnaire, the Peer Interaction Skills Scale, and the Emotion Management Skills Questionnaire. The results show that: (1) Authoritarian parenting style negatively predicted children's emotion management skills, self-control, and peer interactions; (2) Authoritative parenting style positively predicted children's emotion management skills, self-control, and peer interactions; (3) Structural equation models indicated that self-control and peer interactions partially mediated the effects of authoritarian and authoritative parenting styles. The parenting style of Chinese children aged 3-6 years is related to emotion management skills, and self-control and peer interactions have chain mediating effects between parenting style and children's emotion management skills. These results provide further guidance for the prevention and intervention of emotional and mental health problems in children.